Narcological status of patients with schizotypal disorder and comorbid affective pathology - Pliekhov, V. A.; Плєхов, Владислав Андрійович (Запорізький державний медичний університет, 2022)
The purpose: to identify the features of the narcological status of patients with schizotypal disorder and comorbid affective pathology.
Keywords: тези доповідей